2002
DOI: 10.1002/jmv.10081
|View full text |Cite
|
Sign up to set email alerts
|

Endemic hepatitis C virus infection in a Sicilian town: Further evidence for iatrogenic transmission

Abstract: The prevalence of and risk factors for HCV and HBV infections in the general population and the predictive value of ALT screening in identifying anti-HCV positive subjects have been evaluated in a small Sicilian town. A random 1:4 sampling from the census of the general population was performed. Anti-HCV, HCV-RNA, HCV genotype, HBsAg, and anti-HBc were tested. The linkage between HCV infection and potential risk factors was evaluated by multiple logistic regression analysis. Among 721 subjects studied, 75 (10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
5
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 18 publications
(25 reference statements)
8
58
5
3
Order By: Relevance
“…the low prevalence of anti-Hcv antibodies among older persons in the united states is most likely due to a cohort effect and the risk of acquiring Hcv infection lower in the distant past rather than the recent past. in Kenya, the risk was the same, higher in the recent past than the distant an observation that is different from that observed and reported in cameroon (4) and italy (5).…”
Section: Figure 1 Infection Among Different Age Groupscontrasting
confidence: 89%
“…the low prevalence of anti-Hcv antibodies among older persons in the united states is most likely due to a cohort effect and the risk of acquiring Hcv infection lower in the distant past rather than the recent past. in Kenya, the risk was the same, higher in the recent past than the distant an observation that is different from that observed and reported in cameroon (4) and italy (5).…”
Section: Figure 1 Infection Among Different Age Groupscontrasting
confidence: 89%
“…Healthcare settings have several potential parenteral contributors to HCV transmission, with blood transfusion, surgery, dental treatment, acupuncture and therapeutic injections (especially with nondisposable syringes), and high frequency of injection documented as independent predictors of HCV infection [18,20,23,[26][27][28][29][30]. Those who had ever been in a hospital were 2.1 to 3.7 times more likely to have acquired HCV [20,26,[28][29][30][31][32]. In our study, participants who had more than one hospital admission were found to be 7.2 times more likely to have HCV than those who had never been admitted.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience the majority (nearly half of cases) of untreated patients were older that 65 years of age, with 75% over 70 years and thus likely not suitable for treatment. This is a serious treatment barrier to overcome even at a national level, because it reflects the epidemiological pattern of HCV infection common in all Italian areas as shown by several population-based surveys [10][11][12][13]. However, it should be considered that we are treating the patient and not the virus, in order to prevent HCV-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%